Post‐translational modification of Streptococcus sanguinis SpxB influences protein solubility and H2O2 production. (3rd August 2021) - Mu, Rong; Anderson, David; Merritt, Justin; Wu, Hui; Kreth, Jens
Abstract: Streptococcal pyruvate oxidase (SpxB) is a hydrogen peroxide‐generating enzyme and plays a critical role in Streptococcus sanguinis interspecies interactions, but less is known about its biochemistry. We examined SpxB subcellular localization using protein fractionation and microscopy and found SpxB to be primarily cytoplasmic, but a small portion is also membrane associated. Potential post‐translational modifications of SpxB were determined using coimmunoprecipitation and mass spectrometry. Two mutant strains were constructed to further validate the presence of predicted site‐specific post‐translational modifications. These site mutated SpxB proteins exhibited reduced solubility in vivo, which likely contributes to the observed phenotypic changes in colony morphology, bacterial growth, and H2 O2 production. Overall, our data suggest that SpxB post‐translational modifications likely play a major role to regulate SpxB function in S. sanguinis .